(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
The vast and well-preserved necropolis areas in Hierapolis hold several tombs which belonged to members of the local Jewish community. Most of the 27 pertaining epitaphs are perfectly within the scope of local (i.e. pagan) traditions and habits. One text, however, clearly stands out: The sarcophagus inscription of Tatianus and Apphia, Ioudaioi, contains several remarkable features which call for closer consideration. Most of them pertain to the sphere of legal history in the Roman East or, more specifically, to rare peculiarities within the widespread system of tomb protection in Asia Minor: the concession of rights to a sarcophagus from husband to wife, an oddly phrased prohibition against unwarranted burials, the involvement of both a private individual and a public institution in a tomb’s protection, and a uniquely designed „clause of official recording“. The text’s most striking feature, however, deals with the couple’s transferral into „ancestral soil“ (patrōa gē)—with no further specification given on the stone. The article examines all these highly irregular features one by one in the context of Jewish and pagan epitaphs from Hierapolis and beyond. Special regard is given to the couple’s idea of „ancestral soil“, which, as is shown in detail, may well have been Judaea. The text, thus, may deliver early evidence for the wish of Diaspora Jews to be transferred there after death.